The Effect Of Roa, Cr, And Der On Stock Prices In The Food And Beverage Sector Listed On The Indonesian Stock Exchange (Bei) In 2018-2022 - Boby Nata Kusuma; Mohamad Iqbal Syafeiq; Rupi’ah Rupi’ah; Erwin Budianto (Journal Of Social Science (JoSS), 2024)
The purpose of this study is to ascertain how the food and beverage industry companies listed on the Indonesia Stock Exchange (IDX) are affected by return on assets, debt-to-equity ratios, and current ratios. The Multiple Linear Regression technique and Purposive Sampling of 23 companies over a 5-year research period are applied to secondary data. The SPSS software, version 29, was used to conduct this investigation. They discovered that stock prices are negatively impacted by ROA and CR but not by DER. Then, stock prices are simultaneously impacted by CR, DER, and ROA.